Review of commercial nuclear fusion projects - Meschini, Samuele; Laviano, Francesco; Ledda, Federico; Pettinari, Davide; Testoni, Raffella; Torsello, Daniele; Panella, Bruno (Frontiers in Energy Research, 2023)
Nuclear fusion technologies have re-gained momentum in the last decade thanks to their disruptive potential in different fields, such as energy production and space propulsion, and to new technological developments, especially high temperature superconductor tapes, that allow overcoming previous performance or design limits. To date, reviews of recent nuclear fusion designs are lacking. Therefore, this paper aims at giving a comprehensive overview of nuclear fusion concepts for industrial applications with a focus on the private sector. The designs are classified according to the three leading concepts for plasma confinement, namely magnetic confinement, inertial confinement and magneto-inertial confinement. The working principles of the main devices are described in detail to highlight strengths and weaknesses of the different designs. The importance of the public sector on private projects is discussed. The technological maturity is estimated, and the main criticalities for each project are identified. Finally, the geographical distribution of the companies (or public institutions) pursuing the design of fusion devices for commercial applications is reported.